Classification of cross site scripting web pages using machine learning techniques - Al-Answer, Faisal Saleh Nasser, 1981-, author 610938; Fakulti Kejuruteraan. Sekolah Komputeran 619086 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis Sarjana Sains (Keselamatan Maklumat)